UZBEK TELEVISION DURING THE PERIOD OF RESTRUCTURING (PERESTROIKA) - Rakhmatullaeva, Ilmira (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2020)
The article examines the activities of Uzbek television during the period of restructuring in the former Soviet Union and analyzes its contribution to the development of telejournalism during the years of restructuring, its influence on telejournalistic trends. The policy of openness and democratization initiated by M. S. Gorbachev has created favorable conditions for mass media, including television. Openness (Glasnost) significantly weakened censorship: persecutions for discussing current political issues were lifted, previously "closed" topics of Soviet history were addressed, paving the way for addressing shortcomings hindering its implementation. The new policy expanded journalistic possibilities. During this period, live broadcasts, televised debates, teleconferences, new programs, formats, and genres were created on television, new programs and emerging figures became known.
Keywords: television; restructuring; freedom of speech; openness; publicistic performances; teleconference; author's program of telethon